Analisis Strategis Berbasis SWOT terhadap UMKM Dewi Songket di Kecamatan X Koto, Kabupaten Tanah Datar - Febriani, Aisyah; Intan Denata; Shinta Ayu Wulandari; Nuzul Khaira; Aditia Rahman (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study was carried out due to the absence of suitable management strategies for Dewi Songket Pandai Sikek MSMEs, resulting in the company’s suboptimal development. Thus, an effective approach is required to grow the Dewi Songket Pandai Sikek company. This study is a qualitative descriptive analysis that emphasizes SWOT analysis to help the owners of Dewi Songket Pandai Sikek MSMEs enhance their business management. The methods for gathering data in this research included observation, interviews, and the examination of documents. This research employed a SWOT matrix, leading to the development of the W-T strategy, which is a method that leverages weaknesses as opportunities. The execution of this strategy involves providing training, hiring young individuals from Pandai Sikek, and creating new ideas for fashion products made from songket.